Eco-Frauds: The Ethics and Impact of Corporate Greenwashing - SIMION, Radu (Studia Universitatis Babeș-Bolyai Philosophia, 2024)
The evolving dynamics of the marketplace, coupled with concerns regarding the finite capacity to meet increasing demands, have led to the emergence of new phenomena and practices. These developments, while heralding significant changes in the perception and selection of products and services, also elicit substantial concerns. Greenwashing is defined as the strategic practice by which corporations create a misleading impression of their environmental initiatives. This paper examines the theoretical foundations and multifaceted nature of greenwashing, identifying key deceptive strategies such as hidden trade-offs, lack of verifiable evidence, vagueness, irrelevance, and false labels. It explores the motivations behind greenwashing, which often stem from the pressure to appear environmentally responsible without incurring the costs associated with genuine sustainability. The analysis underscores the broader implications of greenwashing, including its impact on consumer trust, corporate governance, and environmental policy. Additionally, the paper addresses the emerging issue of "machinewashing," wherein companies make exaggerated claims about the ethical aspects of their AI technologies. Furthermore, the concept of environmental vices is explored, illustrating how greenwashing perpetuates unethical behaviors and undermines authentic sustainability efforts. To address these practices, the study advocates for a comprehensive approach that includes stricter regulations, increased transparency, and greater engagement from civil society. By promoting genuine sustainability and holding corporations accountable, it is possible to restore consumer trust and support authentic environmental initiatives, thereby fostering a more sustainable and ethical commerce.